Associations between rushed condom application and condom use errors and problems. (12th November 2014) - Crosby, Richard; Graham, Cynthia; Milhausen, Robin; Sanders, Stephanie; Yarber, William; Shrier, Lydia A
Abstract : Objective: To determine whether any of four condom use errors/problems occurred more frequently when condom application was 'rushed' among a clinic-based sample from three US states. Methods: A convenience sample (n=512) completed daily electronic assessments including questions about condom use being rushed and also assessed condom breakage, slippage, leakage and incomplete use. Results: Of 8856 events, 6.5% (n=574) occurred when application was rushed. When events involved rushed condom application, the estimated odds of breakage and slippage were almost doubled (estimated OR (EOR)=1.90 and EOR=1.86). Rushed application increased the odds of not using condoms throughout sex (EOR=1.33) and nearly tripled the odds of leakage (EOR=2.96). With one exception, all tests for interactions between gender and rushed application and between age and rushed application were not significant (p values>0.10). Conclusions: This event-level analysis suggests that women and men who perceive that condom application was rushed are more likely to experience errors/problems during the sexual event that substantially compromise the protective value of condoms against disease and pregnancy. Educational efforts emphasising the need to allow ample time for condom application may benefit this population.